Aura phenomenon: a proposal for an etiology-based clinical classification - Umberto Pensato; Andrew M. Demchuk; Jens P. Dreier; Kevin C. Brennan; Simona Sacco; Michele Romoli (The Journal of Headache and Pain)
Abstract Background The term “aura” refers to a well-defined pattern of usually positive, progressive, and reversible neurological symptoms, with spreading depolarization as the underlying mechanism. While commonly associated with migraine, aura can also occur in other neurological disorders (i.e., cerebrovascular disorders). However, current terminology inadequately describes its different underlying clinical etiologies. Main body We propose the following terminology and etiology-based clinical classification for the aura phenomenon: (i) Migrainous Aura (when the etiology is migraine), (ii) Non-migrainous Aura (when there is an alternative etiology), (iii) Aura of uncertain clinical etiology (when etiology is unclear), and (iv) Migrainous Infarction (a typical migrainous aura in a patient with migraine with aura associated with an infarction in a corresponding anatomical brain region). Conclusion This nuanced classification aims to aid in the diagnostic evaluation and phenotyping of aura phenomenon, ultimately improving the diagnosis and management of the different associated neurological conditions. Moreover, it could promote effective communication and translational mechanistic research.